Reviving Arab reform : development challenges and opportunities (Emerald Publishing Limited, 2021)
Reviving Arab Reform offers a unique consideration of the links between economic, political and social development in the Arab region and offers tangible hope for the future. Islam Abdelbary evaluates the reform programmes in the last three decades in the Middle East North Africa region, and through a wide variety of analytical methods, he identifies the failures and successes of previous Arab reforms by comparing the outcomes of reforms in the Arab world with those in other world regions. The book is distinguished by how it outlines the challenges and opportunities for development in the region and provides a framework for comprehensive and integrated development in the Arab world. Ultimately, Abdelbary argues that the new Arab reform agenda must address previous debilitating development issues, especially governance. Economic reform should not be seen in a vacuum, in isolation from political and social choices that society makes, thereby contributing to sustained and inclusive growth. For its unique mix of scholarly rigour and practical ways forward, Reviving Arab Reform is a must-read not only for researchers interested in economic theory, development studies, and the Middle East but also for policy-makers in the region and international organisations.